The upholding of employee rights in Zimbabwe: an analysis of the private security sector from 2009- 2015 - Mapfumo, Talkmore Fanuel (Midlands State University, 2017)
This research seeks to examine the upholding of employee rights in Zimbabwe and to see what has been done to promote employee rights particularly in the private security sector. After there were widespread reports of unfair labour practices in the country with employers taking advantage of the economic crises in the country to abuse employee rights. The abuse of employee rights dates back to the colonial era and even after independence which had been achieved with the support of trade unions. Thus, a complete uphold of employee rights remains a pipe-dream. Employers’ motives are driven by profit and employees’ motivation is driven by salary maximization, job security and incentives. The failure to pay wages, forcing employees to work overtime, non-payment of terminal benefits, closing down of companies without paying terminal benefits and other factors constitute unfair labour practice. This research, therefore, is aimed at examining the major factors underlying the failure to uphold employee rights in Zimbabwe’s industries and, later own, give suggestions and recommendations that can guarantee the upholding of employee rights. The research was qualitative in nature and focus and will use four companies that are in the private security sector and their employees as a case study. Information from trade unions and the National Employment Council – Security Industry (NEC-SI) was also used since these are the major players in the upholding of employee rights. Thus, their contributions played a huge part in the research. The outcome of the study will certainly contribute towards a panacea to the problems affecting the environment of work in Zimbabwe in coming up with measures and policies that address these challenges.